Simultaneous Analysis of P53 Protein Expression and Cell Proliferation in Irradiated Human Lymphocytes by Flow Cytometry - Rafael de Freitas e Silva; Neyliane Frassinetti Gonçalves dos Santos; Valéria Rêgo Alves Pereira; Ademir Amaral (SAGE Publishing, 2014)
P53 protein has an intrinsic role in modulating the cellular response against DNA radioinduced damages and has been pointed out as an indirect indicator of individual radiosensitivity. The rate of cell proliferation is also a parameter that has been related to tissue sensitivity to radiation. However, this feature is yet understudied. In this context, the aim of this work was to employ Flow Cytometry (FC) for simultaneously assessing of p53 protein expression levels together with cellular proliferation rate of irradiated human lymphocytes. From in vitro irradiated human blood samples, mononuclear cells were isolated and labeled with Carboxylfluorescein Diacetate Succinimidyl Ester (CFSE) prior to phytohaemagglutinin (PHA) stimulation in culture for 96 hours. Cells were also labeled with anti-p53 monoclonal antibody PE-conjugated in order to analyze either proliferation rate or p53 expression levels by FC. It was verified a reduction in the proliferation rate of irradiated lymphocytes and, in parallel, a rise in the p53 expression levels, similar for quiescent and proliferating lymphocytes. The results emphasize the importance of the use of CFSE-stained lymphocytes in assays associated to proliferation rate and the use of this methodology in several studies, such as for evaluating individual radiosensitivity.